Moderating effects of human resource management practices and entrepreneur training on innovation and small-medium firm performance - Mohd Rosli Mohamad; Rosman Mahmood (Sciedu Press, 2013)
A large number of studies on innovation can be found in the literature, yet until recently, research on the moderating effects of HRM practices and entrepreneur training on the relationship between innovation and firm performance are nonexistent. This study attempts to address the questions of how HRM practices and entrepreneur training interact with innovation, which then affect SMF performance. Two hundred eighty-four samples were obtained from SMFs in Malaysia. This study found that the employee and employer training interacted with innovation and significantly influenced SMF performance. Theoretically, greater performance of SMFs is not merely explained by how much they put their effort in innovation, but also how much they invest in employee and employer training. This also reminds the SMFs that innovation and training of both employee and entrepreneur must go hand in hand, so that their performance could be enhanced.